1 Estimasi Biaya Pembangunan Modular Kontainer Sebagai Bangunan Shelter di Kabupaten Banyuwangi - Rahmatin, Esti Putri; Wiryasuta, I Ketut Hendra; Pradita, Rahayu (UKI Press, 2024)
ABSTRACT Banyuwangi Regency is one of the areas prone to natural disasters. According to data from the Regional Disaster Management Agency (BPBD) of Banyuwangi Regency, the disasters that occurred in 2022 resulted in significant damage to infrastructure and forced residents to evacuate. In response to these events, BPBD took several measures, including setting up communal kitchens and planning temporary shelters. Providing safe, durable, and easily transportable shelters is an initial step in disaster mitigation, considering the unpredictable timing and impact of disasters. Modular container units are easily transportable and modifiable, making them suitable for use as shelter buildings. However, in Banyuwangi Regency, there has been no prior use of used containers for evacuation purposes, necessitating a cost estimation. Therefore, this research aims to determine the estimated cost required for the construction of modular container shelters in Banyuwangi Regency. The use of used containers serves as an alternative solution for constructing shelters that are more effective, efficient, and sustainable, despite requiring some improvements. The methodology employed in this research involves interviews with container contractors and AHSP to estimate costs. The results of this study provide an estimated cost for the construction of container shelters. The total estimated cost for constructing modular container shelters within one evacuation area amounts to Rp2,696,817,000.00. The cost breakdown for each task is as follows: construction of container shelter work costs Rp2,377,973,350.58, container shelter transportation costs Rp288,288,000.00, preparation work costs Rp9,612,548.22, and dismantling and installation work costs Rp20,943,200.00. Keywords: Cost, Estimation, Modular container, Shelter